The use of thermal imaging for monitoring the training progress of professional male sweep rowers - Straburzynska-Lupa, A., Korman, P., Sliwicka, E., Krysciak, J., Ogurkowska, M. B. (Scientific Reports, 2022)
This study assesses the thermal profile of the skin in highly trained rowers and investigates the relationship between resting skin temperature (Ts) and the muscle peak torque (PT) measured in statics at the beginning (autumn) and the end (spring) of the preparatory period. Ten professional male sweep rowers, members of the Polish national rowing team, were investigated. A thermal imaging camera was used to analyze the Ts. The PT of the muscles involved in the rowing cycle were measured isometrically. No significant temperature asymmetries were found, except in front of arms after exercise in the spring (p = 0.0228). In contrast, the PT test in the autumn confirmed the significant asymmetry of the knee joint extensors (p = 0.0192). In spring compared to autumn, Ts in many areas of the body were slightly higher, as was PT of underlying muscles. Significant correlations between resting Ts and PT of the underlying muscles were found. Thermal imaging makes it possible to observe changes in skin temperature and symmetry before and after exercise. At this stage, it does not appear to be a method that, without supporting of other methods such as those assessing muscle function, will allow monitoring of training progress.